Penerapan Model Pembelajaran Kooperatif Tipe NHT (Numbered Head Together) Menggunakan Rangkaian Limbah Detergen Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Energi - Devi Ratnasari; Muhammad Yakob (Jurnal Pendidikan Fisika dan Sains, 2020)
Learning undertaken to achieve the educational goals and objectives of national development in general. To achieve the goal of education is carried out of learning by using learning models. The learning model should be involving the students actively in the teaching and learning activities, in order to improve learning outcomes. The purpose of this study is determine the learning outcomes of students with cooperative learning model type NHT (Numbered Head Together) using a series of waste detergents on the material energy. The method used in this research is experimental research method. Population is this research is as many 198 students of class X IPA which consists of 6 classes. While the sample as many 32 students of class X IPA 5. Based on the results of research in the analysis using the t test showed tcount = 4,03 with the ttable=1,9954 on the significant level of 5%. Because tcount > ttable then it can be concluded that there is an increase student learning outcomes using cooperative learning model type of NHT (Numbered Head Together) on as series of waste detergents on the material energi in the class X IPA 5 SMA Negeri 3 Langsa. Keywords : Cooperative Learning, Model NHT, Waste Detergent